Consumption, productivity and cost: Three dimensions of water and their relationship with the supply of artificial shading for beef cattle in feedlots - Novelli, Taisla Inara; Bium, Bianca Freire; Biffi, Carlos Henrique Cogo [UNESP]; Picharillo, Maria Erika; de Souza, Natália Spolaore [UNESP]; de Medeiros, Sérgio Raposo; Palhares, Julio Cesar Pascale; Martello, Luciane Silva (Elsevier, 2022)
It is important to understand the relationship between beef cattle water performance and animal welfare. However, to date, there is no knowledge of studies carried out to assess the water productivity of cattle when using an animal welfare practice. This study aimed to evaluate the impact of artificial shading in the water intake and water productivity and the relationships between these indicators with animal performance and water cost in a cattle feedlot system. Animals were divided into two groups, with shade (GS) and without shade (GWS), and they were housed in four collective pens. Water intake (WI, L day−1), dry matter intake (DMI, kg day−1), and average daily gain (ADG, kg day−1) were obtained for all cattle individually. To calculate water productivity, water input was the direct technical water represented by animal drinking. The average daily water intake for animals under shade was 36.8 L day-1. Animals without shade consumed 9% (3.3 L day−1) more water than animals under shade. Animals under shade presented higher water productivities. The average water productivity per kilograms of live weight of animals under shade was 0.203 kg LW L−1 water, with a maximum of 0.264 kg LW L−1 water and a minimum of 0.159 kg LW L−1 water. These values were 0.185, 0.234, and 0.097 kg LW L−1 water, respectively, for animals without shade. This is justified due to the lower average water intake for these animals and due to the numerically higher live weight and carcass weights. The results showed that if a production system uses shade in the feedlot, the water payment could be reduced by 7.2%. The study demonstrated that animals had a benefit by being produced with better welfare, the environment has a benefit by producing the same output with less water input, and the consumer wins by having an available product with environmental and animal welfare values.
Keywords: Artificial shade; Climate changes; Drinking water; Meat; Water saving